Corporate Social Responsibility with the Local Community as Assessed by Employees in the SME sector: An Empirical Study - Elżbieta MARCINKOWSKA; Joanna SAWICKA (Communications of International Proceedings, 2022)
This article presents an assessment of CSR (Corporate Social Responsibility ) activities in the area of cooperation with the local community made by employees from the SME sector. The aim of the survey was to provide answers as to which activities in the area of cooperation with the local community are important for employees working in SME companies. If so, does the position occupied and the gender of the employees matter for the evaluation of these activities within the CSR strategy. The survey was conducted on a sample of 618 respondents, employees of SME companies that formally or informally have a CSR policy. This survey is part of a broader study on CSR in the SME sector. The data was collected from the 618 SME employees in Poland through questionnaires, which were analysed with the IBM SPSS Statistics 26.0. Our survey results provide evidence that, according to employees, the CSR activities proposed in terms of cooperation with the local community are important and should be carried out by companies in the SME sector. Employees considered all the proposed activities such as improving local infrastructure, support of local institutions in the form of financial, in-kind or service (employee volunteering), social integration, environmental activities or employee volunteering to be important, regardless of their position. These are important findings, as they show that companies in the SME sector should engage in CSR activities.
Keywords: CSR; employees; local community; SME companies.